Coproduction in commissioning decisions: is there an association with decision satisfaction for commissioners working in the NHS? A cross-sectional survey 2010/2011. Issue 6 (5th June 2014) - Taylor-Phillips, Sian; Clarke, Aileen; Grove, Amy; Swan, Jacky; Parsons, Helen; Gkeredakis, Emmanouil; Mills, Penny; Powell, John; Nicolini, Davide; Roginski, Claudia; Scarbrough, Harry
Abstract : Objectives: To undertake an assessment of the association between coproduction and satisfaction with decisions made for local healthcare communities. Design: A coproduction scale was developed and tested to measure individual National Health Service (NHS) commissioners' satisfaction with commissioning decisions. Setting: 11 English Primary Care Trusts in 2010–2011. Participants: Staff employed at NHS band 7 or above involved in commissioning decisions in the NHS. 345/440 (78%) of participants completed part of all of the survey. Main outcome measure: Reliability and validity of a coproduction scale were assessed using a correlation-based principal component analysis model with direct oblimin rotation. Multilevel modelling was used to predict decision satisfaction. Results: The analysis revealed that coproduction consisted of three principal components: productive discussion, information and dealing with uncertainty. Higher decision satisfaction was associated with smaller decisions, more productive discussion, decisions where information was readily available to use and those where decision-making tools were more often used. Conclusions: The research indicated that coproduction may be an important factor for satisfaction with decision-making in the commissioning of healthcare services.